2016
DOI: 10.1177/1049731516641492
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Mental Health–Related Stigma of Social Work Students

Abstract: The aim of this study was to evaluate the impact of a social contact and education intervention to improve attitudes to mental illness in first-year social work students. This was a 3-month cluster randomized controlled trial with two parallel arms: intervention (87) and control group (79). The intervention was a workshop led by an OBERTAMENT activist (a person with a mental illness trained in communication skills and empowerment by a social worker). We assessed intended future behavior toward people with ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Considering as possible universes all primary care and mental health centres (children and adolescents, adults and substance abuse) in Catalonia and the effect sizes of an intervention carried out with social work students [34], using a similar methodology, the number of participants was estimated according to the following calculation of statistical power. Accepting an alpha risk of 0.05 and a beta risk of 0.2 in a two-sided test, assuming a correlation between the first and second measure of r = 0.6., 99 subjects were considered necessary in each group to recognize as statistically significant difference greater than or equal to 0.4 standard deviations.…”
Section: Participantsmentioning
confidence: 99%
“…Considering as possible universes all primary care and mental health centres (children and adolescents, adults and substance abuse) in Catalonia and the effect sizes of an intervention carried out with social work students [34], using a similar methodology, the number of participants was estimated according to the following calculation of statistical power. Accepting an alpha risk of 0.05 and a beta risk of 0.2 in a two-sided test, assuming a correlation between the first and second measure of r = 0.6., 99 subjects were considered necessary in each group to recognize as statistically significant difference greater than or equal to 0.4 standard deviations.…”
Section: Participantsmentioning
confidence: 99%
“…As noted, Rubio-Valera et al (2016) revealed almost one third of social work students participating in workshops on mental health stigma had experienced mental health issues themselves, while Covarrubias and Han (2011) identified that social work students may enter their programmes with stigmatising attitudes toward people with mental illness, and Newcomb et al (2017) reported social work students' reluctance to disclose their past service-user status. Taken together, this literature suggests that many students may understand the lived experience of mental ill-health, and training can equip them with skills and knowledge to recognise, and work to reduce, mental health stigma for service users.…”
Section: Qualitative Researchmentioning
confidence: 99%
“…Similarly, research by Rubio-Valera et al (2016) revealed almost one third of social work students participating in workshops on mental health stigma had experienced mental health concerns themselves. Yet Covarrubias and Han (2011) identified that many students entering social work programmes held stigmatising attitudes toward people with mental illness.…”
Section: Social Work Students Emotional Exhaustion and Mental Healthmentioning
confidence: 99%
“…Considering effect sizes of an intervention carried out with social work students [16], using a similar methodology, the number of participants was estimated according to the following calculation of statistical power. Accepting an alpha risk of .05 and a beta risk of .2 in a two-sided test, assuming a correlation between the first and second measure of r = 0.6., 99 subjects were considered necessary in each group to recognize as statistically significant difference greater than or equal to 0.4 standard deviations.…”
Section: Participantsmentioning
confidence: 99%